Antimicrobial Blue Light Inactivation of Neisseria gonorrhoeae: Roles of Wavelength, Endogenous Photosensitizer, Oxygen, and Reactive Oxygen Species - Wang, Ying (Lasers Surg Med, 2019)
BACKGROUND AND OBJECTIVES: The aim of this study was to investigate the efficacy, safety, and mechanism of action of antimicrobial blue light (aBL) for the inactivation of Neisseria gonorrhoeae, the etiological agent of gonorrhea. STUDY DESIGN/MATERIALS AND METHODS: The susceptibilities of N. gonorrhoeae (ATCC 700825) in planktonic suspensions to aBL at 405- and 470-nm wavelengths were compared. The roles of oxygen in the anti-gonococcal activity of aBL were studied by examining the effects of hypoxic condition (blowing N(2)) on the anti-gonococcal efficiency of 405-nm aBL. The presence, identification, and quantification of endogenous photosensitizers in N. gonorrhoeae cells and human vaginal epithelial cells (VK2/E6E7 cells) were determined using fluorescence spectroscopy and ultra-performance liquid chromatography (UPLC). Finally, the selectivity of aBL inactivation of N. gonorrhoeae over the host cells were investigated by irradiating the co-cultures of N. gonorrhoeae and human vaginal epithelial cells using 405-nm aBL. RESULTS: About 3.12-log(10) reduction of bacterial colony forming units (CFU) was achieved by 27 J/cm(2) exposure at 405 nm, while about 3.70-log(10) reduction of bacterial CFU was achieved by 234 J/cm(2) exposure at 470 nm. The anti-gonococcal efficacy of 405-nm aBL was significantly suppressed under hypoxic condition. Spectroscopic and UPLC analyses revealed the presence of endogenous porphyrins and flavins in N. gonorrhoeae. The concentrations of endogenous photosensitizers in N. gonorrhoeae (ATCC 700825) cells were more than 10 times higher than those in the VK2/E6E7 cells. In the co-cultures of N. gonorrhoeae and VK2/E6E7 cells, 405-nm aBL at 108 J/cm(2) preferentially inactivated N. gonorrhoeae cells while sparing the vaginal epithelial cells. CONCLUSIONS: aBL at 405-nm wavelength is more effective than 470-nm wavelength in inactivating N. gonorrhoeae while sparing the vaginal epithelial cells. Reactive oxygen species generated from the photochemical reactions between aBL and endogenous photosensitizers play a vital role in the anti-gonococcal activity of 405-nm aBL. Lasers Surg. Med.